BRS 374 - wheat cultivar - Caierão,Eduardo (2013)
BRS 374 is a wheat cultivar developed by Embrapa. It resulted from a cross between the F1 generation of PF 88618/Coker80.33 and Frontana/Karl. BRS 374 belongs to the soft wheat class, has a low plant height, a high potential grain yield, and white flour.